Targeting epigenetic alterations in cancer stem cells - F., Verona; V. D., Pantina; C., Modica; M., Lo Iacono; C., D’Accardo; G., Porcelli; D., Cricchio; A., Turdo; M., Gaggianesi; S., Di Franco; M., Todaro; V., Veschi; et al. (Frontiers in Molecular Medicine, 2022)
Oncogenes or tumor suppressor genes are rarely mutated in several pediatric tumors and some early stage adult cancers. This suggests that an aberrant epigenetic reprogramming may crucially affect the tumorigenesis of these tumors. Compelling evidence support the hypothesis that cancer stem cells (CSCs), a cell subpopulation within the tumor bulk characterized by self-renewal capacity, metastatic potential and chemo-resistance, may derive from normal stem cells (NSCs) upon an epigenetic deregulation. Thus, a better understanding of the specific epigenetic alterations driving the transformation from NSCs into CSCs may help to identify efficacious treatments to target this aggressive subpopulation. Moreover, deepening the knowledge about these alterations may represent the framework to design novel therapeutic approaches also in the field of regenerative medicine in which bioengineering of NSCs has been evaluated. Here, we provide a broad overview about: 1) the role of aberrant epigenetic modifications contributing to CSC initiation, formation and maintenance, 2) the epigenetic inhibitors in clinical trial able to specifically target the CSC subpopulation, and 3) epigenetic drugs and stem cells used in regenerative medicine for cancer and diseases.